Louise Bourgeois drawings & observations - Bourgeois, Louise 1911-2010 (Univ. Art Museum and Pacific Film Archive [u.a.], 1995)
Though known primarily for her sculpture, Louise Bourgeois has displayed a lifelong passion for drawing and considers it to be essential to her oeuvre. This exceptional book is the first to combine over fifty years of the artist's drawings with her own observations. Not merely preparatory studies for her sculptures, Bourgeois's drawings are fully realized, independent works of art that rank as some of her most powerful and emotive creations. In the text accompanying the illustrations, Bourgeois, a highly autobiographical artist, describes and explains the sources for each work - and in the process provides fascinating insights into her life and art.
Keywords: Bourgeois, Louise <1911->; Bourgeois, Louise <1911-> - Expositions; Bourgeois, Louise <1911-2010>; Bourgeois, Louise <1911-2010> -- Exhibitions; Bourgeois, Louise -- 1911-2010; Tekeningen; Zeichnung; Ausstellungskatalog -- 1996 -- Berkeley Calif.